PARTISIPASI MASYARAKAT DALAM PELAYANAN PUBLIK DI KECAMATAN PRAYA KABUPATEN LOMBOK TENGAH - Siahaan, Jannus Timbo Halomoan; Lalu Budiman (Bajang Institute, 2026)
Abstract: Public participation in the provision of public services is one of the important requirements in realizing good governance. This study aims to analyze public participation in public services in Praya District, Central Lombok Regency. The main problem is the low level of citizen involvement in official forums for policy formulation, although informal participation is quite active. The research method uses a qualitative approach with in-depth interviews, observations, and document reviews. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results of the study indicate that: 1) The form of public participation is still dominated by labor and social participation, not policy participation; 2) Factors that influence participation include economic busyness, low understanding, time constraints, and bureaucratic design; 3) Implications for service quality are seen in the still limited space for dialogue and public oversight of public services. These results confirm the existence of a research gap between normative regulations on public participation and empirical practices at the sub-district level. Therefore, a strategy for strengthening participation that is more contextual, inclusive, and based on the real needs of the Praya District community is needed. The recommendations are as follows: 1) The Praya District Government needs to establish a policy of public service information transparency that is easily accessible, simple, and based on community needs; 2) Strengthening community participation cannot be done partially, but must be done through an integrated and sustainable approach; 3) The Praya District Government needs to implement policies based on a specific conceptual model. Praya Sub-district is expected to be able to transform community participation from merely symbolic involvement to substantive participation that has a direct impact on the quality of public services.